An Exploration Of A Social Capital Concept In Novice Principals Of Boyolali District - Siti Nurjaningsih (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The success of school principals in leading their schools is influenced by various factors, one of which is social capital. Beginner school principals in Boyolali Regency face unique challenges in managing social capital as they are just starting their leadership careers. This study explores the concept of social capital among beginner school principals in Boyolali Regency. The research method used is qualitative, with data collection techniques involving literature review and structured interviews. The data were analyzed in three stages: data reduction, presentation, and conclusion drawing. The study results indicate that schools with strong social capital support student-oriented learning through collaboration with various parties, such as local SMEs, health centers, and local communities. Social capital is integrated into intra-, co-, and extracurricular activities, enhancing holistic student development. Teachers' involvement in community social activities strengthens the school's relationship with its surrounding environment. In conclusion, beginner school principals' utilization of social capital is crucial in creating a school culture that comprehensively supports student learning.